A study of maternal near miss at a district teaching hospital: a retrospective observational study - S., Manjunatha; T. N., Harsha; H. R., Damayanthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal health is an integral part of health care system. Maternal mortality is an indicator of maternal health and health care delivery system. Severe morbid conditions require comprehensive approach. Hence the concept of Maternal Near Miss (MNM) has emerged. The data of maternal near miss helps to reduce the maternal death and helps to achieve the goals related to reduce the maternal mortality rate of the country as well as the world and to improve the quality of life of the woman population by a quality care. Objectives of present study were to identify and analyze the strategies undertaken in the management of maternal near miss and outcome, measures to improve the quality of care and to assess the various indicators of MNM. Methods: With the permission from the hospital administrators and after taking the ethical clearance from the institutional ethical committee, a retrospective observational study was conducted for the period of one year between January 2016 to December 2016 at district teaching hospital of Kodagu Institute of Medical Sciences, Madikeri, by collecting data from hospital records. Admissions to the ICU as well as wards which fit in to the WHO maternal near miss criteria were included and studied. Results: WHO criteria for the MNM was followed. In present study, there were 25 MNM cases and four Maternal Deaths out of 3347 live births giving a maternal mortality ratio of 119/100000 live births (LB), Maternal Near Miss ratio of 7.46/1000LB, MNM:1MD ratio is 6.25 and mortality index (MI) is 13.79%. Twenty five cases of obstetric emergencies with serious concerns for maternal health were selected out of 97 cases who met the WHO criteria for MNM (25.77%). Twelve cases (48%) received multiple blood-transfusions, 8 cases (32%) of sepsis, 7 (28%) of PPH, and 5 (20%) of hypertensive disorder of pregnancy (pre-eclampsia, eclampsia). There were 12 cases (48%) that had more than one inclusion criteria. Surgical intervention was required in 8 (32%) i.e. 2 peripartum hysterectomies, 2 laparotomies, 1 manual removal of placenta, 1 uterine reposition and 2 traumatic PPH repair. Conclusions: Maternal-Near-Miss (MNM/SAMM) and its relation to maternal mortality contribute as sensitive measures of pregnancy outcome than mortality alone. Proper documentation is of paramount importance in analysis of data, to make conclusions and recommendation. Prospective structured study is required to get a clear picture and to suggest corrective measures which can be taken as far as obstetric care is concerned, to reduce maternal mortality and to achieve the sustainable developmental Goal (SDG) of maternal mortality ratio <70/100000 LB by 2030.